Public policy and participation in political interest groups: An analysis of minimum wages, labor unions, and effective advocacy - Michael R. Strain; Jeffrey Clemens (American Enterprise Institute (AEI), 2020)
Why do individuals join interest groups?
Keywords: A; 330; Labor Unions; Minimum Wage; Public Opinion; Special Interests; US Economy; US Labor Market